2011
DOI: 10.15407/spqeo14.03.302
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of quaternary chalcogenide As-Ge-Te-Si thin films

Abstract: Abstract. Investigated in this paper is the effect of replacement of Te by Si on the optical gap and some other physical operation parameters of quaternary chalcogenide (where x = 0, 5, 10, 12 and 20 at.%) thin films. Thin films with the thickness 100-200 nm of were prepared using thermal evaporation of bulk samples. Increasing Si content was found to affect the average heat of atomization, average coordination number, number of constraints and cohesive energy of the alloys. Optical absorption is due to allowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This coordinative number, N co is a good factor used to find out some details about the covalent bonds of the atomic units, especially for the chalcogenide non-crystalline compositions. 33,53,55 Ioffe and Redel 56 suggested that the nearest neighbor atoms' bonding nature in chalcogenide compositions can be easily defined by knowing this substantial number. The glassy compositional structure can also be studied based on topological concepts through the continuous random network model.…”
Section: ( ) = −mentioning
confidence: 99%
See 1 more Smart Citation
“…This coordinative number, N co is a good factor used to find out some details about the covalent bonds of the atomic units, especially for the chalcogenide non-crystalline compositions. 33,53,55 Ioffe and Redel 56 suggested that the nearest neighbor atoms' bonding nature in chalcogenide compositions can be easily defined by knowing this substantial number. The glassy compositional structure can also be studied based on topological concepts through the continuous random network model.…”
Section: ( ) = −mentioning
confidence: 99%
“…This model complies with the number of outer shell electrons, which are in principle 8 electrons. [54][55][56] Consequently, this essential number, N co can be computed from Eq. 14, after that listed in Table V.…”
Section: ( ) = −mentioning
confidence: 99%